The Influence of Company Size, Independent Commissioners, Leverage, Managerial Ownership, and Institutional Ownership on the Integrity of Financial Statements - Febiana, Dyah Ayu Putri; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of Company Size, Independent Commissioners, Leverage, Managerial Ownership and Institutional Ownership on the Integrity of Financial Statements in Banking Companies Listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The population in this study is banking companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023, namely 43 companies, using the purposive sampling technique obtained from 14 companies, so that the number of samples used is 42 observation data. The analysis used in this study is multiple linear regression using SPSS version 26 as the calculation tool. Based on the results obtained in this study, it is shown that company size, independent commissioners, managerial ownership, and institutional ownership have no effect on the integrity of financial statements. Meanwhile, leverage has a positive effect on the integrity of financial statements.